Long-term performance of dual-listed companies in mainland China and Hong Kong - Wu, Yiwei (2013)
The long-run underperformance of initial public offering (IPO) that has been commonly documented in many previous literatures. The investigation of dual-listed stocks is one of the most popular topics about IPO in the world wide range. This paper studies the long-term post performance of dual-listed stocks in mainland China and HK stock markets by using 48 Chinese mainland based companies over the period of January 1993 to August 2010. Consistent with Guo et al. (2010), Foerster and Karolyi (1993), Serra (1999) and Lee (1992)’s findings in various stock markets, an apparent underperformance also been found for these dual-listed IPOs in mainland China and HK in a three-year observation period. The regression result of the last dummy variable, exchange, indicates the long-term abnormal returns are different in two markets. When looking at them separately, stocks listed in HK even experience a worse aftermarket performance (-29.66%) than in Chinese mainland (-5.67%). In addition, eight explanatory variables that identified from several typical and relevant theories have combined with the unique features of each market to provide a comprehensive explanation on underperformance.